European Industrial Relations. A Resource for the Reconstruction of the American System - Barkin, Solomon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
European industrial relations Systems have in the last two decades been creative and expansive and intimately integrated into their respective national economic, political and social fabric. Their experience provides a revitalized source of information on the roles of trades unions and collective bargaining in a democratic state and as a countervailing force to the power of business both on the national and international scenes.